Multimedia Encryption and Watermarking - Furht, Borko. (Multimedia Systems and Applications ;, 2005)
Multimedia Encryption and Watermarking presents a comprehensive survey of contemporary multimedia encryption and watermarking techniques, which enable a secure exchange of multimedia intellectual property. Part I, Digital Rights Management (DRM) for Multimedia, introduces DRM concepts and models for multimedia content protection, and presents the key players. Part II, Multimedia Cryptography, provides an overview of modern cryptography, with the focus on modern image, video, speech, and audio encryption techniques. This book also provides an advanced concept of visual and audio sharing techniques. Part III, Digital Watermarking, introduces the concept of watermarking for multimedia, classifies watermarking applications, and evaluates various multimedia watermarking concepts and techniques, including digital watermarking techniques for binary images. Multimedia Encryption and Watermarking is designed for researchers and practitioners, as well as scientists and engineers who design and develop systems for the protection of digital multimedia content. This volume is also suitable as a textbook for graduate courses on multimedia security.